Development, Urban Infrastructure and Class-Based Ordering in Cordoba City (Argentina) - Salguero Myers, Katrina Alicia (2024)
The article engages the connections between development and infrastructure in an area of the city of Córdoba, Argentina, called the Fifth Section. From an ideological critique approach, the research examines three urban interventions inaugurated during 2018 and 2019, oriented to achieve fast circulation, urban safety, and social inclusion. The proposal, on one hand, presents a field of interrogations around the concepts of development, ideology and cities. On the other hand, it analyzes three urban infrastructures that materialize social horizons and expectations with a class perspective. The methodological strategy is qualitative and based on journalistic sources, images, official documents and interviews made during field work. The article arrives at conclusions regarding an ideological operation that, based on the idea of development, presents infrastructure as an undeniable benefit that transforms spaces, seals social conflict, and produces social separations/unifications.